2018
DOI: 10.1002/nbm.4017
|View full text |Cite
|
Sign up to set email alerts
|

Ratiometric NOE(−1.6) contrast in brain tumors

Abstract: Recently, a new nuclear Overhauser enhancement (NOE)‐mediated saturation transfer effect at around −1.6 ppm from water, termed NOE(−1.6), was reported to show hypointense signals in brain tumors. Similar to chemical exchange saturation transfer or magnetization transfer (MT) effects, which depend on the solute pool concentration, the exchange/coupling rate, the solute transverse relaxation rate, etc., the NOE(−1.6) effect should also depend on these factors. Since the exchange rate is relevant to tissue pH, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
38
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 71 publications
12
38
2
Order By: Relevance
“…The amplitudes of rNOE(−1.6) in the z-spectra and AREX resid were reduced on the tumor side ( Figure 1 , Figure 2 and Figure 3 ); this finding is consistent with those reported by other studies [ 9 , 19 , 25 ]. Figure 4 presents the AREX resid (−1.6) images and the hematoxylin and filipin staining results together; they indicate that the tumor region was cholesterol-deficit and that the AREX resid (−1.6) in the tumor region was hypointense.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…The amplitudes of rNOE(−1.6) in the z-spectra and AREX resid were reduced on the tumor side ( Figure 1 , Figure 2 and Figure 3 ); this finding is consistent with those reported by other studies [ 9 , 19 , 25 ]. Figure 4 presents the AREX resid (−1.6) images and the hematoxylin and filipin staining results together; they indicate that the tumor region was cholesterol-deficit and that the AREX resid (−1.6) in the tumor region was hypointense.…”
Section: Discussionsupporting
confidence: 92%
“…A minor absorption appeared on the shoulder of the direct saturation at −1.6 ppm, and it was referred to as the choline group from lipids. The normal side had a higher saturation than the tumor side [ 9 , 19 , 25 ], and this difference increased during the experimental period.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…[32][33][34] Previously, we have tentatively assigned the NOE(−1.6) to be from dipolar interactions between phospholipid choline head group protons and water protons. 14,15,19 Recently, we have reported that the NOE(−1.6) signal from rat brain changes significantly with intake of different gases (ie, air, O 2 , and N 2 O), 16 suggesting that the NOE(−1.6) signal may be related to cerebrovascular reactivity. Two other publications also observed the NOE(−1.6) signal in blood.…”
Section: Introductionmentioning
confidence: 99%